Forum: The Why and How of Global Governors: Relational Agency in World Politics. Issue 4 (26th November 2022) - Hofferberth, Matthias; Lambach, Daniel; Koch, Martin; Holzscheiter, Anna; Deloffre, Maryam Zarnegar; Reiners, Nina; Ronit, Karsten
Abstract: Scholars of world politics can readily list the global governors of our time, but why and how did these particular actors gain agency in the first place? While there is impressive scholarship on single global governors and their respective impact, there is little comparative work and systematic theorization on what agency in world politics is and how actors gain it. This forum brings together contributions that apply relational frameworks to the question, focusing on the dynamics of self-agentification, delegation, and recognition. Individual contributions detail different empirical cases, from individuals to the G20, and introduce concepts for meso-level theorizing. Taken together, the contributions call for a more dynamic research agenda that not only allows scholars to reconstruct how agency emerges but also pushes us toward an agency-focused reframing of global governance, which is needed to ensure the continued relevance of the paradigm.